Neuroinflammation in Schizophrenia: A Critical Review and The Future - ARICIOĞLU, FEYZA (KURE ILETISIM GRUBU A S, 2016)
Schizophrenia is a serious mental illness that affects approximately 1% of the population worldwide, with positive, negative and cognitive dysfunctions and a significant deterioration in psychosocial functioning. Interactions between genetic predisposition and environmental stressors at the early stages of life, and subsequently a molecular level neurodegeneration process are important in the development of schizophrenia. Current approaches suggest that cytokines-induced neuroinflammation might have a role in the development of several psychiatric disorders, including schizophrenia. Uncontrolled microglial activation, increase in pro-inflammatory cytokines, and subsequent neurotransmitter dysfunctions can induce schizophrenia. Microglial activation induced by pro-inflammatory cytokines in central nervous system is responsible for the initiation and proceeding of the inflammatory process and consequently developing neurodegeneration. Here in this review, we aimed to provide an overview to the latest findings related to the cytokines-mediated peripheral and central immune responses in the development of schizophrenia.
Keywords: schizophrenia; cytokines; neuroinflammation; DOUBLE-BLIND; CYTOKINE ALTERATIONS; PRENATAL INFECTION; NEGATIVE SYMPTOMS; GLIAL-CELLS; INFLAMMATION; ACTIVATION; HYPOTHESIS; THERAPY; BRAIN